2017
DOI: 10.1186/s41182-017-0061-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk perceptions, attitudes, and knowledge of chikungunya among the public and health professionals: a systematic review

Abstract: BackgroundRecently, attention to chikungunya has increased due to its spread into previously non-endemic areas. Since there is no available treatment or vaccine, most intervention strategies focus on mosquito bite prevention and mosquito control, which require community involvement to be successful. Thus, our objective was to systematically review the global primary literature on the risk perceptions, attitudes, and knowledge of chikungunya among the public and health professionals to inform future research an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 43 publications
1
39
1
1
Order By: Relevance
“…One systematic review showed that risk perceptions, attitudes, and knowledge of chikungunya varied across populations and countries (the review, however, also largely represented Asian regions where the disease is endemic). 30 However, among U.S. populations at risk to vector-borne or infectious diseases, significant relationships have been identified between perceived severity and indicators of heightened risk perception. 10 Additionally, a broad review of protective behavior literature supports the general concept that higher appraisals of perceived risk influence health behavior.…”
Section: Discussionmentioning
confidence: 99%
“…One systematic review showed that risk perceptions, attitudes, and knowledge of chikungunya varied across populations and countries (the review, however, also largely represented Asian regions where the disease is endemic). 30 However, among U.S. populations at risk to vector-borne or infectious diseases, significant relationships have been identified between perceived severity and indicators of heightened risk perception. 10 Additionally, a broad review of protective behavior literature supports the general concept that higher appraisals of perceived risk influence health behavior.…”
Section: Discussionmentioning
confidence: 99%
“…CHIKV disease has symptoms that simulate common symptoms of malaria disease which is the most endemic communicable disease in Sudan and it might mask the presence of Chikungunya [21]. Chikungunya malaria the symptoms of fever, body pain, headache and arthralgia and it should be distinguished by further serological tests [21 Knowing detailed information about the disease and its mode of transmission would control and management strategies particularly among medical students and health related professionals [22]. Most of the study population did not know the morbidity and mortality characteristics of CHIKV disease where the disease has low mortality, high morbidity and economic loss [23].…”
Section: Fig 3 Knowledge Levels About Thementioning
confidence: 99%
“…This is the first study on the perception of the present and future risk of vector-borne diseases (i.e., dengue, [33][34][35][36], H1N1pdm flu [37][38][39] and H5N1 avian flu [40][41][42]; others have focused on general practitioners in France [43][44][45], both general population and practitioners [46], French pharmacists [47] or risk perception in Europe and other countries worldwide [48][49][50]. The appearance of various emerging infectious diseases during the last two decades (e.g., chikungunya, SARS-CoV, MERS-CoV, Ebola virus, Zika), as well as that of antibiotic-resistant bacteria, has stimulated research on risk perception in the general public and policy-makers [51][52][53][54][55].…”
Section: No Studies On the Arboviral Disease Risk Perception By Healtmentioning
confidence: 99%